Zur Rolle gewerblicher Entwicklungen bei der Ermittlung von Wohnflächenbedarfen. Ein interkommunaler Lösungsansatz, illustriert am Beispiel der Region Leipzig/Halle - Sell, Thorben; Henn, Sebastian; Schuchardt, Max (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
Although the functional mix of housing and work promises to create compact settlement structures, the impact of job-creating commercial developments on housing demand is not sufficiently managed in current practice. As a result, there is often an imbalance between housing units and labour force, which is articulated in an increased demand for new land take. The authors take this as a starting point to develop a four-stage model, which is the subject of this article. This model seeks to systematically determine the effects of commercial developments with an impact on jobs on the demand for residential space and to provide a basis for the sustainable management of requirements within the framework of spatial planning. In a first step, the labour force moving in is determined by means of rates of regional mobility and the number of households moving to the area is derived. In a second step, existing commuter structures in the inter-communal context are used to estimate how households should ideally be localised; in the third step, households are then distributed mathematically on the basis of accessibility structures. In the fourth and final step, we articulate a proposal for the efficient realization of demand tailored to distinct housing segments. Finally, the model is applied to the Leipzig/Halle region.